Combustion and emissions from cerium oxide nanoparticle dosed diesel fuel in a high speed diesel research engine under low temperature combustion (LTC) conditions. (15th March 2021) - Leach, Felix C.P.; Davy, Martin; Terry, Barbara
Abstract: Cerium oxide (CeO2 ) is widely used in three-way-catalysts (TWCs) in the catalytic oxidation of hydrocarbons (HC) and carbon monoxide (CO) as well as the catalytic reduction of NOx . It has also had use as a fuel-borne catalyst in diesel fuel – particularly to promote diesel particulate filter (DPF) regeneration. The literature indicates that the catalytic effect of CeO2 might reduce HC emissions, reduce NOx formation, slow burn rates and reduce fuel consumption. In this work 8–10 nm CeO2 particles in diesel are tested at two dosing levels (5.7 & 19.8 mg/L) as a fuel-borne catalyst (FBC) in a modern high speed single cylinder diesel engine at two operating points, one low load and one high load. The combustion and engine-out emissions are analysed and compared to the undosed diesel fuel. The results show that CeO2 reduces soot and THC emissions by up to 30% at part load under LTC but no significant differences are observed at high load. At high load a minor (2–5%) reduction in NOx for a given EGR level is observed. No significant differences are seen in fuel consumption at either load point. At light load, a significant difference in the particulate size distribution is observed with fuels dosed with CeO2 . CeO2 is observed to remove small particles under LTC conditions. In terms of the combustion parameters a reduction in maximum cylinder pressure of 2.5% at part load and an increase in ignition delay of up to 10% at high load are observed.